Some notes on phonological phrasing in Brazilian Portuguese - Sandalo,Filomena (2003)
In this paper, we argue that phonological phrasing in Brazilian Portuguese is determined by the interaction of right-alignment of syntactic and phonological phrases (Selkirk 1986) and a eurythmic factor of Uniformity (Ghini 1993), which prefers p-phrases of equal prosodic length. The Uniformity requirement shows some unexpected properties. It is not tied to a preferred length of p-phrases, and it appears to be restricted to p-phrases overlapping with the subject and the verb of the clause.